Indonesia : peoples and histories - Taylor, Jean Gelman, 1944- (Yale University Press, 2003)
Indonesia is the fourth largest country in the world. It comprises more than 17,000 islands inhabited by 230 million people who speak over 300 different languages. Now the world's largest Muslim nation, Indonesia remains extraordinarily heterogeneous due to the waves of immigration - Buddhist, Hindu, Arab, and European - that have defined the region's history. Fifty years after the collapse of Dutch colonial rule, Indonesia is a nation in the midst of dramatic upheaval. In this broad survey, Jean Gelman Taylor explores the connections between the nation's many communities, and the differences that propel contemporary breakaway movements. Drawing on a broad range of sources, including art, archaeology and literature, Taylor provides a historical overview from the prehistoric period to the present day. The text is enlivened by brief "capsule" histories on topics ranging from pepper to Maharajas to smallpox